The ethnic migrant inventor effect - Choudhury, Prithwiraj; Kim, Do Yoon (Strategic Management Journal, 2019)
[Research Summary: Ethnic migrant inventors may differ from locals in terms of the knowledge they bring to host firms. Using a unique dataset of Chinese and Indian herbal patents filed in the United States, we find that an increase in the supply of first-generation ethnic migrant inventors increases the rate of codification of herbal knowledge at U.S. assignees by 4.5%. Our identification comes from an exogenous shock to the quota of H1B visas and from a list of entities exempted from the shock. We also find that ethnic migrant inventors are more likely to engage in reuse of knowledge previously locked within the cultural context of their home regions, whereas knowledge recombination is more likely to be pursued by teams comprising inventors from other ethnic backgrounds. Managerial Summary: Managers and policy makers around the world face a vigorous debate on whether to hire skilled migrants or hire locals. We argue that if western firms stop hiring ethnic migrants, innovation at these firms would suffer in two ways: knowledge transfer and knowledge recombination would both be impeded. We argue and show that skilled ethnic migrants bring to their employers, unique knowledge from the cultural context of their host country. Also, local inventors engage in “knowledge recombination” by combining their existing knowledge to knowledge transferred by migrants. Our empirical results relate to the patenting of Chinese and Indian herbal formulations at western pharmaceutical firms before and after an immigration shock related to the admittance of skilled migrants from these two countries.]